CCNA voice study guide - Froehlich, Andrew, 1977- (Serious skills., 2010)
"The ultimate guide to the new CCNA voice network administrator certification exam. The new CCNA Voice exam tests candidates on their ability to implement a Cisco VoIP solution. Network administrators of voice systems will appreciate that the CCNA Voice Study Guide focuses completely on the information required by the exam"--Resource description page.